Analysis the Influence of Sharia Compliance, Islamic Financial Literacy, and Risk Perception on Islamic Stock Investment Decisions in the Bibit Application - Nasution, Rahmad Mulia Tama; Harahap, Muhammad Ikhsan; Harahap, Rahmat Daim (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study aims to determine the effect of Sharia Compliance (X1), Sharia Financial Literacy (X2) and Risk Perception (X3) on Sharia Stock Investment Decisions (Y) in the Bibit application, study of students of the Faculty of Economics and Islamic Business UINSU. This study uses a quantitative approach method. The data used in this study are primary data. Data collection in this study used a questionnaire to 100 respondents of FEBI UINSU students who use the Bibit application. The sampling method in this study uses the Slovin formula and the determination of samples / respondents using non-random purposive sampling with the criteria of respondents of FEBI UINSU students who invest in Islamic stocks in the Bibit application. Data processing and analysis using multiple linear regression methods which include data quality tests, classical assumption tests and hypothesis testing. The results showed that simultaneously the influence of X1, X2, X3 had a positive and significant effect on Y, partially only X3 had a positive and significant effect on Y. The results of testing the coefficient of determination R Square of 0.203 or 20.3%, indicate that the independent variable (X) contributes to the influence or is able to explain the dependent variable (Y) or the Islamic stock investment decision in the Bibit application for FEBI UINSU students.